ORAL HEALTH STATUS OF CHILDREN WITH SICKLE CELLS IN KINSHASA, DR CONGO - Kowe DN; Songo BF; Penze NA; Fayeta NB-J; Muzeke AR; Yanga ML; Agbor MA; Pilipili CM; Forna NC (Romanian Society of Oral Rehabilitation, 2022)
Introduction: Sickle cells disease is a genetic blood dyscrasia that is endemic among children in the sub-Saharan sub-region. The objective of our study was to assess the oral health status of children with sickle cell disease in Kinshasa. Methods: A descriptive and multicenter study was conducted in Kinshasa among SS homozygous children aged under 17 years. Sociodemographic data, habits and levels of oral hygiene, snacking, consultations with the dentist, oral clinical examination as well as odontalgia during the vaso-occlusive crises (VOC) constituted the parameters of study. Results: A total of 194 children with sickle cell disease including 114 (58.8%) males and 80(41.2%) females were examined. The results showed that the mean plaque index was PI=1.46±0.89. The prevalence of dental caries was 58.8% and the state of gingival inflammation was 0.7 ≤ GI ≥ 1.9 in 142 (73.2%) children. It was also observed 14.4% of cases of dental structure anomalies such as hypoplasia, 7.21% glossitis, 1.5% fracture of the anterior teeth and 3.6% odontalgia without dental cause during the VOC . Conclusion: Oral problems are also the prerogative of children with sickle cell disease.